2014
DOI: 10.1113/expphysiol.2014.081190
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasomotor reactivity: steady‐state versus transient changes in carbon dioxide tension

Abstract: New FindingsWhat is the central question of this study?The relationship between changes in cerebral blood flow and arterial carbon dioxide tension is used to assess cerebrovascular function. Hypercapnia is generally evoked by two methods, i.e. steady-state and transient increases in carbon dioxide tension. In some cases, the hypercapnia is immediately preceded by a period of hypocapnia. It is unknown whether the cerebrovascular response differs between these methods and whether a period of hypocapnia blunts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…However, the present study included only rebreathing‐induced hypercapnia because recent research (Brothers et al . ) reported that hyperventilation‐induced hypocapnia attenuates the cerebral vasodilatory responses during a subsequent period of rebreathing‐induced hypercapnia. In order to assess the cerebral vasodilatory response without confounding factors caused by a preceding hypocapnic stage, hypocapnia‐induced cerebral vasoconstriction was not assessed in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the present study included only rebreathing‐induced hypercapnia because recent research (Brothers et al . ) reported that hyperventilation‐induced hypocapnia attenuates the cerebral vasodilatory responses during a subsequent period of rebreathing‐induced hypercapnia. In order to assess the cerebral vasodilatory response without confounding factors caused by a preceding hypocapnic stage, hypocapnia‐induced cerebral vasoconstriction was not assessed in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects then performed the rebreathing protocol as previously described (Brothers et al . ; Hurr et al . ,b).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Medical grade oxygen was bled into the bag in order to maintain constant arterial normoxia (S p O 2 = ~97%) during the rebreathing period (Claassen et al. ; Brothers ; Hurr et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…; Brothers et al. ), and variations in end‐tidal CO 2 (ETCO 2 ) significantly contribute to very low frequency (<0.04 Hz) CBF variability (Mitsis et al. ; Peng et al.…”
Section: Introductionmentioning
confidence: 99%